The Influence Of Ta’lim Al-Muta’alim Learning In Improving The Manner Students Class III Regular at TMI Al-Amien Prenduan School Year 2022 - Abdul Hadi; Napisah (CV. Doki Course and Training, 2025)
Ta'lim Al-Muta'lim book is one of the classic books, which until now is still the main reference for many seekers of knowledge in good and correct procedures or etiquette for learning and teaching according to the teachings of the Islamic religion.Manners is one of the sections that include the discussion of morals, that is, all outward or visible behaviors, moral norms, and our daily social procedures in society or fellow human beings. This research is an attempt to find out the influence of learning the Book of Ta'lim Al-Muta'alim in improving the manners of class III Regular A students at TMI Al-Amien Prenduan 2022. The objectives of this study are: (1) To find out the effect of studying the book of Ta'lim Al-Muta'allim on the behavior of students class III Regular A. (2) To know how much influence learning the book of Ta'lim Al-Muta'allim can improve the manners of students class III Regular A. This research is a type of non-experimental research that is part of quantitative research, the authors use correlative research which in this case is used to see the relationship of a variable with other variables. After the researcher assessed the questionnaire, then added it using the product moment formula. Researchers can conclude that there is the influence of studying the book of Ta'lim Al-Muta'allim on the behavior of students in class III Regular A which is worth 0.555 so, the level of correlation is rather low